The Relationship of Adversity Quotient and Religious Culture on Students' Academic Achievement - Fuad, A. Jauhar; Amin, Muhammad Mahrus (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
The achievement of students is determined by their efforts. However, students tend to give up easily and become pessimistic when difficulties increase. This study shows that students tend to give up easily and become pessimistic when difficulties increase. This study aims to analyze the relationship between adversity quotient (AQ) and religious culture on student academic achievement in the Islamic Religious Education (PAI) Study Program. This study is a correlational survey study, with a population of 661 students with an average age of 20. The data scale used a Likert scale. The location of the study was Universitas Islam Tribakti Lirboyo Kediri. The study was conducted on second and fourth-semester students from February to July 2023 using purposive sampling techniques. Data analysis used regression analysis. Based on the calculations obtained, a significant relationship exists between adversity quotient and student academic achievement. There is a significant relationship between religious culture and academic achievement. A significant relationship exists between adversity quotient and religious culture on student academic achievement.